Popular and Elite Religion: Feastdays and Preaching - D'Avray, D. L. (Studies in church history, 2006)
In rejecting the distinction between elite and popular religion, Eamon Duffy’s presidential address echoes a much earlier contribution to Studies in Church History. Arnaldo Momigliano found the dichotomy misleading where Christian historians of Late Antiquity were concerned, as Dermot Fenlon points out later in this volume, showing that the other historians too were thinking along the same lines. In the present volume Professor Duffy makes a similar point with great force for a different time and place, late medieval England. Here and in his Stripping of the Altars the liturgy has a key role in his argument. He observes that Books of Hours or Primers are a form of the monastic office. Taking his thought further on lines he clearly intends, one could argue that the psychology of prayer is similar in the two cases and similar to the rosary also. In all three cases thoughts need not be about the words, for the focus of the prayer may be different, but the words work as a mantra to shut out distractions and create a devout frame of mind.